2012
DOI: 10.1037/a0028820
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot evaluation of an Internet-facilitated cognitive-behavioral intervention for maternal depression.

Abstract: Objective Develop and pilot an Internet-facilitated cognitive-behavioral treatment intervention for depression, tailored to economically disadvantaged mothers of young children. Method Mothers (N = 70) of children enrolled in Head Start, who reported elevated levels of depressive symptoms, were randomized to either the eight-session, Internet-facilitated intervention (Mom-Net) or delayed intervention/facilitated treatment-as-usual (DI/TAU). Outcomes were measured using the Beck Depression Inventory (BDI II; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 62 publications
5
91
0
Order By: Relevance
“…While preliminary evidence suggests that TAICBT is effective for PPD reported by mothers of young children (Sheeber et al 2012), women's perceptions of TAICBT for PDD have not been explored. Thematic analysis of 25 participants' accounts of a TAICBT program suggested that postnatal women generally reported positive experiences with TAICBT but also noted challenges related to TAICBT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While preliminary evidence suggests that TAICBT is effective for PPD reported by mothers of young children (Sheeber et al 2012), women's perceptions of TAICBT for PDD have not been explored. Thematic analysis of 25 participants' accounts of a TAICBT program suggested that postnatal women generally reported positive experiences with TAICBT but also noted challenges related to TAICBT.…”
Section: Discussionmentioning
confidence: 99%
“…Women who participated in the Mom-Net program reported significant improvements on measures of depression and parental satisfaction and efficacy, as well as a reduction in observational indices of harsh parenting behavior (Sheeber et al 2012). Furthermore, attrition was low, with nearly two thirds of women completing all internet-facilitated sessions (Sheeber et al 2012). While participants in the Mom-Net intervention reported satisfaction with the program, perceptions of the program and suggestions for areas of improvement were not examined.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Puckering [37] Observed mother-infant interactions Sheeber [39] Mother aggression/low support (observation); Parent Behavior Inventory (PBI), hostile/coercive (HC) and supportive/ engaged (SE)…”
Section: Mother-child Relationships and Parenting/marital Distressmentioning
confidence: 99%